Restless Legs Syndrome Patients with Early Onset Disease or a Relevant Family History Associated with Pramipexole Ineffectiveness but Not Pregabalin - Ying M; Wang T; Zhang T; Zhai Z; Zhang L (Nature and Science of Sleep, 2025)
Miaofa Ying,1,* Tiantian Wang,2,* Ting Zhang,3 Ziyang Zhai,4 Lisan Zhang5 1Department of Pharmacy, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Pharmacy, Qiantang Campus, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 3Hangzhou Medical College, Hangzhou, People’s Republic of China; 4Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 5Department of Neurology/Center for Sleep Medicine, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lisan Zhang, Department of Neurology/Center for Sleep Medicine, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China, Tel +86 13805752614, Email zls09@zju.edu.cnBackground: Restless legs syndrome (RLS) is a complex condition characterized by significant heterogeneity. Factors that affect medication efficacy remain unclear; different RLS subtypes may respond differently to various drugs.Objective: To identify factors associated with the ineffectiveness of pramipexole and pregabalin in patients with various subtypes of RLS.Methods: This retrospective nested case–control study enrolled 257 RLS patients prescribed pramipexole or pregabalin between March 2019 and April 2024 at the sleep center of Sir Run Run Shaw Hospital. All patients completed a semi-structured questionnaire, underwent polysomnography and laboratory evaluations, and participated in a telephone survey. To represent iron-storage status, one principal component score that included five indicators of peripheral iron metabolism was extracted by principal component analysis. Treatment effectiveness was assessed using the Clinical Global Impression-Improvement (CGI-I) scale, with scores of 1– 3 indicating effective treatment and higher scores reflecting ineffective treatment. Multivariate logistic regression was employed to assess the risk factors (or RLS subtypes) of medication ineffectiveness.Results: Of patients treated with pramipexole, 42.7% (70/164) reported poor outcomes. Early onset RLS (OR = 5.076; 95% CI, 1.836– 14.033) and relevant family history (OR = 4.537; 95% CI, 1.556– 13.437) increased pramipexole ineffectiveness risk. Among pregabalin users, 34.4% (32/93) reported ineffectiveness, which was associated with hemoglobin levels (OR = 1.039; 95% CI, 1.001– 1.079).Conclusion: These findings suggest that RLS patients with familial or early-onset characteristics may represent a distinct subtype that responds preferentially to α 2δ ligands over dopamine agonists, supporting personalized treatment approaches based on clinical phenotyping.Plain Language Summary: Restless legs syndrome (RLS) is a complex condition associated with significant heterogeneity. How can the best medications for RLS patients with different disease characteristics be chosen?This study aimed to identify predictors of treatment response in restless legs syndrome (RLS) by evaluating clinical, polysomnography, and lab results to differentiate the effectiveness of pramipexole versus pregabalin. Key findings revealed that pramipexole ineffectiveness was associated with early-onset RLS and family history, while only low hemoglobin levels were linked to pregabalin ineffectiveness. A subtype of RLS—early-onset patients or patients with a family history—was identified as a risk factor for pramipexole ineffectiveness, but not for pregabalin ineffectiveness.The above findings suggested that the disease subtype of RLS patients may be a critical factor that cannot be ignored when evaluating medication effectiveness. Prospective, randomized controlled trials are needed to evaluate the efficacy of pramipexole and pregabalin in these specific RLS subtypes.Keywords: restless legs syndrome, family history, early onset, pregabalin, pramipexole